Effect of graphene oxide/ poly-L-lactic acid composite scaffold on the biological properties of human dental pulp stem cells - Zailing Qiu; Xuemei Lin; Luning Zou; Weihao Fu; Hongbing Lv (BMC, 2024)
Abstract Background Tissue engineering has attracted recent attention as a promising bone repair and reconstruction approach. Dental pulp stem cells (DPSCs) are pluripotent and can differentiate into bone cells with the correct environment and substrate. Therefore, suitable scaffold materials are essential for fabricating functional three-dimensional (3D) tissue and tissue regeneration. Composite scaffolds consisting of biodegradable polymers are very promising constructs. This study aims to verify the biological function of human DPSCs seeded onto composite scaffolds based on graphene oxide (GO) and poly-L-lactic acid (PLLA). Methods The surface morphology was observed under scanning electron microscopy (SEM). Chemical composition was evaluated with Fourier transform infrared (FTIR) spectroscopy. The biocompatibility of GO/PLLA scaffolds was assessed using phalloidin staining of cytoskeletal actin filaments, live/dead staining, and a CCK-8 assay. The effect of GO/PLLA scaffolds on cell osteogenic differentiation was detected through ALP staining, ALP activity assays, and alizarin red S staining, complemented by quantitative real-time PCR (qRT-PCR) analysis. Results Our data showed that GO and PLLA are successfully integrated and the GO/PLLA scaffolds exhibit favorable bioactivity and biocompatibility towards DPSCs. Additionally, it was observed that the 0.15% GO/PLLA scaffold group promoted DPSC proliferation and osteogenic differentiation by forming more calcium nodules, showing a higher intensity of ALP staining and ALP activity, and enhancing the expression levels of differentiation marker genes RUNX2 and COL1. Conclusions These results demonstrate that the GO/PLLA scaffold is a feasible composite material suitable for cell culture and holds promising applications for oral bone tissue engineering.